RuxCr1-xO2 bimetallic electro-catalytic material, preparation thereof and application of RuxCr1-xO2 bimetallic electro-catalytic material in hydrogen production by acidic OER and PEM electrolysis water
The RuxCr1-xO2 bimetallic electrocatalytic material prepared by solvothermal method and calcination treatment solved the problem of poor catalytic activity of existing Ru-based OER materials under high current and acid conditions, and achieved low-cost and efficient OER catalytic performance .
Patent Information
- Application Number
- CN202411609861.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-23
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing Ru-based OER materials have poor catalytic activity under high current and acidic conditions, and have high precious metal content, resulting in high material cost.
The Ru source, Cr source and structure adjusting agent were reacted in an alkaline environment by solvothermal method, followed by calcination to prepare the RuxCr1-xO2 bimetallic electrocatalytic material. This method constructs a physical and chemical structure suitable for high current and acidic conditions by adjusting the Ru/Cr molar ratio and controlling the calcining conditions.
The prepared RuxCr1-xO2 bimetallic electrocatalytic material exhibits excellent OER catalytic activity under high current and acidic conditions, and reduces the amount of Ru and reduces the cost of the material.
Smart Images

Figure CN119465237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalyst technology, and in particular to the field of OER electrocatalytic materials. Background Art
[0002] In recent years, proton exchange membrane (PEM) water electrolysis has attracted widespread attention due to its many advantages such as high energy efficiency, small gas crossover, and compact structure. In PEM water electrolyzers, OER catalysts must be able to withstand harsh acidic environments, so there are more stringent requirements for OER catalysts. Precious metals iridium (Ir), ruthenium (Ru) and their derivatives are still the best candidates for acidic OER because of their suitable electronic structure and high corrosion and oxidation resistance.
[0003] For example, a Chinese patent document with publication number CN118026300A discloses a method for preparing rhodium-ruthenium binary metal oxide for PEM electrolytic cell anode, which specifically comprises: constructing rhodium-ruthenium binary metal oxide nanoparticles from bottom to top by an impregnation reduction method; maintaining a uniform particle size of the element precursor during the high-temperature reduction step by binding the structural auxiliary agent carbon black; and introducing the electronic auxiliary agent Rh to form a binary metal oxide with the main element Ru, thereby stabilizing the lattice of the nanoparticles while optimizing the electronic structure of the Ru species.
[0004] For another example, Chinese patent document with publication number CN118127561A discloses a rare earth element-doped RuO2 material, a preparation method and an application thereof, wherein the rare earth element-doped RuO2 material has a rutile crystal structure, wherein rare earth atoms occupy the Ru atomic lattice sites of the rutile RuO2 and are distributed in the crystal structure of the material.
[0005] A Chinese patent document with publication number CN116356361A discloses a method for preparing an amorphous IrOx / Ru catalyst for PEM water electrolysis to produce hydrogen, comprising: ultrasonically treating metal ruthenium powder, iridium salt, and isopropanol, stirring to form a solid suspension, adding sodium nitrate powder and mixing evenly; heating and stirring in a water bath at a constant temperature until the liquid evaporates to dryness to obtain a brown-yellow powder; calcining at 350-450° C., adding a perchloric acid solution and ultrasonically treating after natural cooling, and centrifuging to obtain a black solid; and obtaining an amorphous IrOx / Ru catalyst after centrifugal washing and drying.
[0006] In summary, although the existing technology provides some Ru-based OER materials, and these materials can also obtain good OER performance under acidic conditions, the precious metal content of this type of material is still relatively high, and the material cost is still high. In addition, the OER performance of existing materials under high current and acidic conditions still needs to be improved. Summary of the invention
[0007] In view of the problems of high cost, high current, and unsatisfactory OER catalytic activity under acidic conditions in existing Ru-based noble metal-based catalysts, the first object of the present invention is to provide a Ru x Cr 1-x The preparation method of O2 bimetallic electrocatalyst material aims to prepare OER materials with low Ru content and excellent catalytic activity under high current and acidic system.
[0008] The second object of the present invention is to provide Ru obtained by the preparation method x Cr 1-x O2 bimetallic electrocatalytic materials.
[0009] The third object of the present invention is to provide the Ru x Cr 1-x Application of O2 bimetallic electrocatalytic materials as OER catalysts.
[0010] Most of the existing Ru-based OER materials require a combination of multiple metals to achieve ideal results. The OER performance under bimetallic and low Ru ratios is not ideal. In addition, the performance of existing materials under acidic high current is also not ideal. In view of this problem, the present invention has been studied in depth and provides the following technical solutions:
[0011] Ru x Cr 1-x The preparation method of O2 bimetallic electrocatalyst material comprises subjecting a raw material solution containing a Ru source, a Cr source, a structure regulator of formula 1, and a base to a solvothermal reaction, and then calcining the solvothermal product at 300-500°C to obtain;
[0012] Wherein, the Ru / Cr molar ratio in the Ru source and the Cr source is x / 1-x; and the x is 0.5 to 0.7; and the pH of the raw material solution is above 10;
[0013]
[0014] In the formula 1, M is H, Na, K or NH4; R1 and R2 are independently H, amino, hydroxyl, alkoxy, alkylamino or carboxyl.
[0015] The present invention innovatively conducts solvent thermal treatment on the Ru source and Cr source in the said proportion with the assistance of the structure regulator of Formula 1 and at the said pH, and then performs calcination treatment, so as to construct a physicochemical structure adapted for application under high current and acidic conditions, so as to reduce the proportion of Ru and the bimetallic precursor, and still be able to produce a catalytic material with excellent OER activity under high current and acidic conditions.
[0016] In the present invention, the solvothermal reaction of Ru source and Cr source under the conditions of Formula 1 and the pH is the key to constructing the physical and chemical structure required for OER catalysis under high current and acidic conditions. On this basis, the physical and chemical structure of the material can be further optimized by further controlling the molar ratio of Ru / Cr, the structure regulator of Formula 1 and the pH, and the OER performance of the material under high current and acidic conditions can be further enhanced.
[0017] In the present invention, the Ru source is Ru 3+ Water-soluble salts of ions.
[0018] In the present invention, the Cr source is Cr 3+ Water-soluble salts of ions.
[0019] In the present invention, the water-soluble salt may be, for example, at least one of chlorides, nitrates, sulfates, organic acid salts, etc. of the metal element.
[0020] Preferably, the x is 0.55 to 0.65. Studies have shown that at this preferred ratio, it can be combined with other processes to further enhance the OER activity of the prepared material under high current and acidic conditions.
[0021] There is no particular requirement for the molar concentration of the Ru source in the raw material solution, and it may be, for example, 0.01 to 0.1M.
[0022] In the present invention, in Formula 1, R1 is H, and R2 is amino, hydroxyl or carboxyl. The present invention shows that the preferred material of Formula 1 is helpful to further cooperate with other processes, and can further enhance the OER activity of the prepared material under high current and acidic conditions.
[0023] In the present invention, there is no particular requirement for the substitution positions of R1 and R2.
[0024] In the present invention, the ratio of the molar amount of the structure regulator of Formula 1 to the molar amount of the total metal element Ru+Cr in the raw material solution is 0.1 to 1:1, and can further be 0.3 to 0.5:1.
[0025] In the present invention, under the above-mentioned formula 1 and pH, the physicochemical structure of the solvent thermal product can be optimized, thereby facilitating calcination to obtain an OER catalytic material that is suitable for high current and acidic application requirements.
[0026] In the present invention, the base may be an alkali metal hydroxide; preferably at least one of sodium hydroxide and potassium hydroxide.
[0027] Preferably, the pH of the raw material solution is 10-13.5, and may further be 10-11.
[0028] Preferably, the solvent in the raw material solution is an aqueous solvent, preferably water, or a mixed solvent of water and a water-soluble organic solvent.
[0029] In the present invention, the solvent heat temperature is above 100°C, preferably 130 to 180°C;
[0030] Preferably, the solvent thermal time is more than 10 hours, preferably 10 to 15 hours.
[0031] In the present invention, the calcination stage is carried out in an oxygen-containing atmosphere.
[0032] Preferably, the oxygen-containing atmosphere is air.
[0033] Preferably, the calcination temperature is 350-450°C.
[0034] Preferably, the calcination time is 1 to 6 hours, and further can be 3 to 5 hours.
[0035] The present invention also provides a Ru prepared by the preparation method. x Cr 1-x O2 bimetallic electrocatalytic materials.
[0036] The preparation method described in the present invention can give the prepared material special structural and active exposure characteristics, and the material prepared by the preparation method can adapt to large current and acidic catalytic requirements, and can still obtain excellent OER catalytic performance under such working conditions.
[0037] The present invention also provides a Ru prepared by the preparation method. x Cr 1-x Application of O2 bimetallic electrocatalytic materials, using them as OER catalytic materials.
[0038] Preferably, it is used as an OER catalytic material in an acidic system.
[0039] Preferably, it is used to prepare proton exchange membrane water electrolysis to produce hydrogen.
[0040] The present invention also provides a PEM water electrolysis hydrogen production device, which comprises Ru prepared by the preparation method of the present invention. x Cr 1-x O2 bimetallic electrocatalytic material, or through the Ru x Cr 1-x O2 bimetallic electrocatalytic material was prepared.
[0041] In the present invention, the Ru x Cr 1-x O2 bimetallic electrocatalytic materials are used to prepare the required OER catalytic devices.
[0042] Beneficial Effects
[0043] The present invention innovatively performs solvent thermal treatment on the Ru source and Cr source in the said ratio with the assistance of the structure adjusting agent of Formula 1 and at the said pH, and then performs calcination treatment, so that a bimetallic OER catalyst with a low Ru content can be prepared, and the said catalyst can unexpectedly adapt to the requirements of high current and acidic catalysis, and can still obtain excellent OER catalytic activity under high current and acidic system.
[0044] The present invention also shows that further optimization of the structure of Formula 1, calcination mechanism and other processes can further improve the OER catalytic performance of the prepared materials under high current and acidic conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0045]
Figure 1
[0046]
Figure 2
[0047]
Figure 3
[0048]
Figure 4
[0049]
Figure 5
[0050] The following specific embodiments are intended to further illustrate the present invention in detail, rather than to further limit the scope of protection of the claims of the present invention.
[0051] The reagents involved in the following examples, unless otherwise specified, are commercial reagents purchased directly from the market.
[0052] An optional Ru of the present invention x Cr1-x A method for preparing an O2 catalytic material, the method comprising the following steps:
[0053] S1: mixing a ruthenium source, a chromium source, a structure regulator of Formula 1, a base and a solvent (an aqueous solvent, such as water) to obtain a solution, and subjecting the mixed solution to ultrasound;
[0054] S2: hydrothermal reaction of the mixed solution after ultrasound;
[0055] S3: centrifuging the mixed solution after the reaction and collecting the precipitate;
[0056] S4: drying the precipitate;
[0057] S5: Annealing the dried precipitate to obtain Ru x Cr 1-x O2 catalyst.
[0058] As a preferred solution, the Ru x Cr 1-x The molar ratio of ruthenium to chromium in the O2 catalyst is x:1-x 1-2:1-2. x Cr 1-x The O2 catalyst has the best oxygen evolution catalytic performance when the ruthenium:chromium ratio is 1.5:1, and the ruthenium dosage is greatly reduced compared with the existing precious metal-based catalysts.
[0059] As a preferred technical solution, the ruthenium source is any one of hydrated ruthenium chloride and chlororuthenic acid; the chromium source is any one of chromium nitrate and chromium chloride;
[0060] The structure modifier of Formula 1 may further be at least one of Formula 1A and Formula 1B.
[0061]
[0062] As a preferred technical solution, the hydrothermal reaction time is 12 to 15 hours, and the hydrothermal reaction temperature is 130 to 180°C.
[0063] As a preferred technical solution, the annealing process is: in an air atmosphere, heating to 300°C to 500°C at a heating rate of 2°C / min to 5°C / min, and keeping the temperature for 1 to 6 hours.
[0064] The following is a specific implementation plan:
[0065] Example 1
[0066] Step 1: Preparation of mixed solution:
[0067] Preparation of the mixed solution: 3 mmol of hydrated ruthenium chloride, 2 mmol of chromium nitrate, and 2 mmol of a structure regulator (Formula 1B) were weighed according to a molar ratio of Ru:Cr=1.5:1, and then added to 150 mL of deionized water and mixed evenly, 5 mmol of sodium hydroxide was added to adjust the pH to 10, and the solution was sonicated for 10 minutes to obtain a mixed solution A.
[0068] Step 2: Hydrothermal treatment:
[0069] The obtained mixed solution A was placed in a reactor, heated at a heating rate of 5°C / min, maintained at 150°C for 12 hours, and then naturally cooled to room temperature.
[0070] Step 3: Centrifugal drying:
[0071] The hydrothermal material was washed and centrifuged twice with N,N-dimethylformamide DMF and ethanol respectively, and then placed in an oven at 80°C to dry for 8 hours.
[0072] Step 4: Annealing:
[0073] The material obtained in step 3 was ground and placed in a muffle furnace. In an air atmosphere, the temperature was raised to 400°C (marked as T) at a heating rate of 5°C / min. After being kept at this temperature for 4 hours, it was naturally cooled to room temperature to complete annealing. The catalytic material obtained in this example was named Ru 0.6 Cr 0.4 O2.
[0074] Electrochemical detection
[0075] Take 2 mg of the prepared Ru x Cr 1-x O2 catalytic material (Ru 0.6 Cr 0.4 O2) was dispersed in a mixture of 280 μL ethanol, 200 μL distilled water, and 20 μL 5 wt% nafion solution. After half an hour of ultrasonication, 50 μL of the mixed solution was dropped on carbon paper. After natural drying, Ru was tested using an electrochemical workstation. x Cr 1-x The electrochemical performance of the O2 catalyst was tested in an acidic environment using a saturated calomel electrode as the reference electrode, a platinum sheet as the counter electrode, and 0.5M H2SO4 as the electrolyte at a scan rate of 5mV / s. The stability test was performed by chronopotentiometry at 100mA / cm 2 The test was carried out at a current density of .
[0076] PEM polarization test: First, 20 mg Ru x Cr 1-xThe O2 catalytic material was dispersed in 3 mL of deionized water and ultrasonically dispersed for 30 minutes; then it was ball-milled for 25 minutes using a ball mill, and then 100 μL of naphthol (5 wt.%) and 1 mL of isopropanol were added and ultrasonically dispersed for 30 minutes, and then it was evenly sprayed on a single cathode (platinum carbon) electrolytic electrode (purchased from Shengerno) as an anode membrane electrode using a spray gun. The prepared membrane electrode was assembled into a PEM water electrolyzer for performance evaluation. Note: The gas diffusion layer is titanium felt, the test temperature is 80 ° C, and the active area is 1 cm 2 .
[0077] Example 2
[0078] Compared with Example 1, the only difference is that the molar ratio of Ru to Cr is controlled to be: Ru:Cr=2:1, and the total metal molar amount of Ru and Cr and other operations and parameters are the same as Example 1.
[0079] Example 3
[0080] Compared with Example 1, the only difference is that the molar ratio of Ru to Cr is controlled to be: Ru:Cr=1:1, and the total metal molar amount of Ru and Cr and other operations and parameters are the same as Example 1.
[0081] Example 4
[0082] Compared with Example 1, the only difference is that the conditions of steps 1 and 2 are changed, and the experimental groups are:
[0083] Group A: Changing the structural modifier to Formula 1A;
[0084] Group B: In step 1, the pH was 11, the amount of Formula 1B was 2.5 mmol, the hydrothermal temperature was changed to 160°C, and the hydrothermal time was 10 h;
[0085] Other operations and parameters are the same as in Example 1.
[0086] Example 5
[0087] Compared with Example 1, the only difference is that the process of step 4 is changed, and the specific groups are:
[0088] Group A: annealing temperature T is 300℃;
[0089] Group B: annealing temperature T is 500℃, time is 3h;
[0090] Other operations and parameters are the same as in Example 1.
[0091] Comparative Example 1
[0092] Compared with Example 1, the only difference is that chromium nitrate is not added, and the molar amount of the remaining Ru is the same as the total molar amount of Ru+Cr in Example 1, and the other operations and parameters are the same as Example 1.
[0093] Comparative Example 2
[0094] Compared with Example 1, the only difference is that ruthenium chloride is not added, and the molar amount of the remaining Cr is the same as the total molar amount of Ru+Cr in Example 1, and the other operations and parameters are the same as Example 1.
[0095] Comparative Example 3
[0096] Compared with Example 1, the only difference is that in step 1, the pH of the raw material solution is 9, and the other operations and parameters are the same as in Example 1.
[0097] Comparative Example 4
[0098] Compared with Example 1, the only difference is that in step 1, an equimolar amount of sodium ethylenediaminetetraacetate is used to replace the structure adjusting agent, and other operations and parameters are the same as those in Example 1.
[0099] Comparative Example 5
[0100] Compared with Example 1, the only difference is that Ru is not added in step 1 but is added in step 3, that is, the Ru source is lacking in step 1, and the product of step 1 lacking the Ru source is treated in step 2, and then in step 3, the hydrothermal product containing only Cr and ruthenium are mixed in step 3 and then treated in step 4. Other operations and parameters are the same as in Example 1.
[0101] Table 1 Current density is 100mA / cm 2 Oxygen evolution potential test results
[0102] <![CDATA[Overpotential (100 mA / cm 2 )]]> Example 1 298mV Example 2 338mV Example 3 364mV Example 4-A 325mV Example 4-B 304mV Example 5-A 372mV Example 5-B 351mV Comparative Example 1 437mV Comparative Example 2 / Comparative Example 3 395mV Comparative Example 4 379mV Comparative Example 5 421mV
[0103] Table 1 Electrochemical performance of each catalyst
[0104] As shown in Table 1, the overpotential of the catalyst is the lowest when the molar ratio of ruthenium chloride hydrate to chromium nitrate is 1.5:1. 2 The overpotential is 298 mV, which shows that 1.5:1 is the optimal molar ratio of hydrated ruthenium chloride and chromium nitrate.
[0105] As shown in Table 1, compared with Comparative Examples 1-5, the catalyst prepared in Example 1 has a 2 The lowest overpotential at the current density is only 298 mV, indicating that the catalyst material provided by the present invention has good electrocatalytic OER performance.
[0106] like Figure 4 As shown, compared with the catalyst prepared in Comparative Example 4 in which the structure regulator of Formula 1 is replaced with sodium ethylenediaminetetraacetate, the catalyst prepared in Example 1 has a higher conductivity than that prepared in Example 1 at 100 mA / cm 2 At a current density of 1.34 W, the stable catalysis can still be maintained for more than 6 h, which shows that Ru 0.6 Cr 0.4 O2 has good catalytic stability.
[0107] like Figure 5 As shown, in the PEM electrolysis cell, the current density is 1.0 A cm -2 The required voltage is only 1.85 V, indicating that the catalyst has excellent catalytic performance.
[0108] The above describes the specific implementation of the present invention. However, the present invention is not limited to the above implementation. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Ru x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: A raw material solution containing a Ru source, a Cr source, a structure adjusting agent of Formula 1, and a base is subjected to a solvothermal reaction, and then the solvothermal product is calcined at 300 to 500° C. to obtain; Wherein, the Ru / Cr molar ratio in the Ru source and the Cr source is x / 1-x; and the x is 0.5 to 0.7; and the pH of the raw material solution is above 10; In the formula 1, M is H, Na, K or NH4; R1 and R2 are independently H, amino, hydroxyl, alkoxy, alkylamino or carboxyl.
2. Ru as claimed in claim 1 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: The Ru source is Ru 3+ Water-soluble salts of ions; Preferably, the Cr source is Cr 3+ Water-soluble salts of ions; Preferably, the x is 0.55 to 0.65; Preferably, the molar concentration of the Ru source in the raw material solution is 0.01-0.1M.
3. Ru as claimed in claim 1 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: In the formula 1, R1 is H, and R2 is amino, hydroxyl or carboxyl.
4. Ru as claimed in claim 1 or 3 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: The ratio of the molar amount of the structure regulator of formula 1 to the molar amount of the total metal elements Ru+Cr in the raw material solution is 0.1 to 1:
1.
5. Ru as claimed in claim 1 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: The base is an alkali metal hydroxide; preferably at least one of sodium hydroxide and potassium hydroxide; Preferably, the pH of the raw material solution is 10 to 13.5; Preferably, the solvent in the raw material solution is an aqueous solvent, preferably water, or a mixed solvent of water and a water-soluble organic solvent.
6. Ru as claimed in claim 1 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: The solvent heat temperature is above 100°C, preferably 130 to 180°C; Preferably, the solvent thermal time is more than 10 hours, preferably 10 to 15 hours.
7. Ru as claimed in claim 1 x Cr 1-x The method for preparing an O2 bimetallic electrocatalytic material is characterized in that: The calcination stage is carried out in an oxygen-containing atmosphere; Preferably, the oxygen-containing atmosphere is air; Preferably, the calcination temperature is 350-450°C; Preferably, the calcination time is 1 to 6 hours.
8. Ru obtained by the preparation method according to any one of claims 1 to 7 x Cr 1-x O2 bimetallic electrocatalytic materials.
9. Ru obtained by the preparation method according to any one of claims 1 to 7 x Cr 1-x The application of O2 bimetallic electrocatalytic material is characterized by: Use it as OER catalytic material; Preferably, it is used as an OER catalytic material in an acidic system; Preferably, it is used to prepare proton exchange membrane water electrolysis to produce hydrogen.
10. A PEM water electrolysis hydrogen production device, characterized in that: Ru obtained by the preparation method according to any one of claims 1 to 7 x Cr 1-x O2 bimetallic electrocatalytic material, or through the Ru x Cr 1-x O2 bimetallic electrocatalytic material was prepared.
Citation Information
Patent Citations
CrO2-RuO2 solid solution material and preparation method and application as acid OER electrocatalyst thereof
CN109453772A
Composite
GB2565044A
Cited By
Amorphous / crystal RuO2 / WOX-SO4 < 2-> composite material, PEM water electrolysis device, preparation of PEM water electrolysis device and application of PEM water electrolysis device in water electrolysis hydrogen production
CN120905719A
Efficient integrated assembly for PEM exchange membrane water electrolysis hydrogen production system and application of efficient integrated assembly
CN121381024A